Implementation of Evaluation of Kirkpatrick Model in Statistics Course Based on Case Method at the Department of Building Engineering - Zulkifli Matondang; Harun Sitompul; Kinanti Wijaya (Jurnal Penelitian Pendidikan IPA, 2023)
This study aims to obtain an overview of the implementation of Kirkpatrick's evaluation in case-based statistics courses based on Case Method at the Department of Building Engineering. Case-based lectures train students to solve problems in the field of statistics by applying higher-order thinking such as: finding solutions to problems, thinking critically, logically, reflectively, metacognitively and creatively. The evaluation of the Kirkpatrick model is carried out through four levels, and each level is assessed using a different tool. The implementation of Kirkpatrick's evaluation consists of 4 levels, namely: reaction, learning, behavior, and impact. This research method is descriptive qualitative research. The research sample is 56 students majoring in Engineering Building Engineering, State University of Medan. The research data was collected using a questionnaire, assessment and documentation. The questionnaire used has gone through reliability testing with Crombach's Alpha. The assessment was conducted to obtain student performance in the form of learning processes and behavior change. Documentation is obtained through the resulting lecture products. The results showed that Kirkpatrick's evaluation model in statistics course lectures was very effective in revealing the quality of learning. At the reaction evaluation level, students gave a positive response with satisfactory qualifications to case-based statistics lectures. The results of the evaluation at the learning level obtained the difference in learning outcomes on students' thinking abilities of 7.59 with a significance of 0.010. The results of the evaluation at the behavioral level, students have various competencies obtained such as: instrument preparation, instrument analysis, research data processing, SPSS application and interpretation of SPSS analysis results. The results of the evaluation at the impact level are that students are able to compile instruments, obtain and process data used to compose a final project. Based on the criteria for the success of Kirkpatrick's evaluation performance, the implementation of case-based statistics lectures was very successful. Kirkpatrick's evaluation model is able to describe evaluation results that cover all aspects of lectures so that it is worthy of being recommended as an evaluation model for lectures